The Acceptance of Government Resource Planning System Using UTAUT 2 - Muhardi Saputra; Berlian Maulidya Izzati; Jannatul Rahmadiani (Faculty of Computer Science Universitas Indonesia, 2021)
Government Resource Planning (GRP) system is a solution for managing all the resources that exist in government, namely people, technology, and business processes in it. This study aims to analyses how the acceptance of the Service and Licensing Information System for the Public (SIMPATIK) in the Investment Board and Integrated Licensing (DPMPTSP) of West Java Province. This study uses UTAUT 2 model that consist of six independent variables and two dependant variables. The relationship between the independent variable and the dependent variable is moderated by age, gender, and experience variables. The data used are primary data obtained from distributing questionnaires online to 42 DPMPTSP employees that using SIMPATIK. The hypothesis was tested with the SmartPLS and SPSS applications. The results show from a total of 14 hypotheses there are 3 hypotheses that have a significant or acceptable effect, while 11 other hypotheses are not significant or cannot be accepted.